2017
DOI: 10.1039/c6ra26395j
|View full text |Cite
|
Sign up to set email alerts
|

In situ DRIFTS study of the NO + CO reaction on Fe–Co binary metal oxides over activated semi-coke supports

Abstract: Activated semi-coke loaded with Fe and Co species by a hydrothermal method exhibited excellent CO-deNOx performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…The pyrolysis process reduced the amount of carbon and triggered the complete disappearance of N, probably due to the formation of volatile compounds such as NO, NO 2 , and N 2 O 5 [42]. In fact, heating at 500 • C and acidic activation promoted the evolution of H and O from SW to H 2 O and H 2, rather than CO, CO 2 , and hydrocarbons leading to a net reduction of oxygen [43].…”
Section: Characterization Of the Adsorbentsmentioning
confidence: 99%
“…The pyrolysis process reduced the amount of carbon and triggered the complete disappearance of N, probably due to the formation of volatile compounds such as NO, NO 2 , and N 2 O 5 [42]. In fact, heating at 500 • C and acidic activation promoted the evolution of H and O from SW to H 2 O and H 2, rather than CO, CO 2 , and hydrocarbons leading to a net reduction of oxygen [43].…”
Section: Characterization Of the Adsorbentsmentioning
confidence: 99%
“…According to the previous study, the bidentate carbonates were the main adsorption product of CO on the catalyst surface, 52 so it could be concluded that the adsorption of carbon monoxide was inhibited by water vapor. And according to the path of NO + CO reaction over Fe-Co/ASC catalyst, 52 the less adsorbed CO caused the less consumption of the nitrate species on the catalyst surface. Therefore, the NO + CO reaction was inhibited by water vapor, which caused a low NO reduction of the catalyst.…”
Section: àmentioning
confidence: 99%
“…In fact, Cu-, [14][15][16][17][18][19] Co-, [20][21][22] Fe-, 13 Ni-, 23 and Mn-based 14,24 oxides, as either loaded or non-loaded catalysts, exhibit excellent CO-deNO efficiency at temperatures between 150 and 300 C. Furthermore, CeO 2 , SnO 2 , or ZrO 2 mixed with transition metals and carbon supported metal catalysts also promote the efficient reaction of CO with NO. 17,[25][26][27] As for the mechanism of the NO + CO reaction, it is established that at relatively low temperatures, NO coordinates with the metal cation and generates nitrites. 5,13,28 Subsequently, the formed nitrites can react with CO to yield N 2 O and CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…5,28 However, as the temperature increases, the coordinated NO is transformed to nitrates that react with CO, generating N 2 and CO 2 . 5,13,27,28 In our previous study, CO-deNO (catalyzed by semi-coke based catalysts) were applied to a NO x adsorption-reduction process, and the deNO efficiency was relatively high. 5,9,27 However, in this process, SO 2 can be adsorbed onto the adsorbents more easily than NO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation